The Influence of Occupational Safety, Health, And Security Standards On Increasing The Productivity of High-Rise Building Glass Cleaning Workers - Aura Prizi, Jeane; Puspitaloka Mahadewi, Erlina (International Journal of Science, Technology & Management, 2025)
Occupational Safety and Health (OHS) is a crucial element in the modern workplace, particularly in high-rise building cleaning, as effective OHS implementation has been proven to reduce workplace accident rates and simultaneously increase workforce productivity. This study aims to analyze how the implementation of OHS management and VR-AR-based OHS training can affect workplace accident rates and ultimately impact low work productivity due to the high number of falls from height. This study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The subjects in this study included employees who had worked for more than 4 months in the field of high-rise building cleaning in the West Jakarta area. To obtain an appropriate number of respondents, the data collection process was carried out through the distribution of online questionnaires using Google Forms. The instrument trial stage was carried out involving 30 respondents for the initial test, while the total data collected during the main questionnaire filing stage amounted to 130 respondents. The results of the study indicate that the Implementation of OHS Requirements, OHS Management, and VR-AR-Based OHS Training have an impact on Workplace Accidents. Meanwhile, the Implementation of K3 Requirements, VR-AR Based K3 Training, and Work Accidents have an impact on Productivity.